2012
DOI: 10.4049/jimmunol.1102836
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 and β-Catenin Regulate Bone Homeostasis by Controlling the Rate of Osteoclastogenesis

Abstract: TREM2 is an immunoreceptor expressed on osteoclasts (OC) and microglia that transmit intracellular signals through the adapter DAP12. Individuals with genetic mutations inactivating TREM2 or DAP12 develop the Nasu-Hakola disease (NHD) with cystic-like lesions of the bone and brain demyelination that lead to fractures and presenile dementia. The mechanism of this disease is poorly understood. Here, we report that TREM2-deficient mice have an osteopenic phenotype reminiscent of NHD. In vitro, lack of TREM2 impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 45 publications
5
146
1
Order By: Relevance
“…Although we did not observe increased osteoclastogenesis of Fzd8-deficient bone marrow cells ex vivo, neither in the absence nor in the presence of Wnt3a, we were able to demonstrate that canonical Wnt signaling inhibits osteoclastogenesis independent of Opg production by osteoblasts, which was finally confirmed through the generation of mice lacking -catenin in the osteoclast lineage. At that point it is important to state that two other studies have been published at the time of our analysis where Lysm-Cre mediated inactivation of -catenin has been reported to cause osteopenia due to increased osteoclastogenesis (Wei et al, 2011;Otero et al, 2012). However, although both studies provided evidence for a direct inhibitory effect of canonical Wnt signaling on osteoclast formation, they did not demonstrate that -catenin signaling and Opg production were unaffected in osteoblasts in these mice.…”
Section: Discussioncontrasting
confidence: 45%
“…Although we did not observe increased osteoclastogenesis of Fzd8-deficient bone marrow cells ex vivo, neither in the absence nor in the presence of Wnt3a, we were able to demonstrate that canonical Wnt signaling inhibits osteoclastogenesis independent of Opg production by osteoblasts, which was finally confirmed through the generation of mice lacking -catenin in the osteoclast lineage. At that point it is important to state that two other studies have been published at the time of our analysis where Lysm-Cre mediated inactivation of -catenin has been reported to cause osteopenia due to increased osteoclastogenesis (Wei et al, 2011;Otero et al, 2012). However, although both studies provided evidence for a direct inhibitory effect of canonical Wnt signaling on osteoclast formation, they did not demonstrate that -catenin signaling and Opg production were unaffected in osteoblasts in these mice.…”
Section: Discussioncontrasting
confidence: 45%
“…Further genetic studies with β-catenin and other Wnt ligands using various mouse models provided additional evidence that corroborate the critical function of Wnt signaling in skeletal development and bone homeostasis (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Several recent studies also reported that Wnt signaling directly regulates osteoclast function (18)(19)(20)(21)(22). Despite the established function of Wnt signaling in bone, the role of specific Wnt ligands in human bone homeostasis was not clear.…”
Section: Introductionmentioning
confidence: 88%
“…How TREM2 mediates the induction of these multiple gene programs remains unclear. Given that TREM2 and DAP12 promote macrophage survival in the presence of limited concentrations of CSF-1 (11,46) and that CSF-1 production in the brain may be limited, especially during neuronal and glial damage, TREM2-deficient microglia may be unfit overall and hence dysfunctional; they simply may not be sufficiently robust to activate the multiple programs required for an effective response to myelin damage. Alternatively, TREM2 may be required as a coreceptor for other activating receptors.…”
Section: Discussionmentioning
confidence: 99%